Grounded theory for qualitative research a practical guide - Urquhart, Cathy (SAGE, 2013)
Based on the author's own wealth of experience this timely, engaging book helps first-time researchers to discover the excitement of grounded theory method. Fresh, innovative and clear, this book traces the history and development of grounded theory method, and examines how the method is evolving for new contexts today. It sets out the principles involved in using grounded theory method and explains the process and theory associated with coding in grounded theory. The book introduces us to the practicalities of research design, theory building, coding and writing up.